Kernel taste inheritance in almond - Vargas F.J.; Romero M.A.; Batlle I. (XI GREMPA Seminar on Pistachios and Almonds, 2001)
Kernel taste (sweet-bitter) has been observed in 4919 seedlings, derived from 152 controlled crosses, using 61 cultivars as parents. The kernel of 4771 seedlings was sweet and 148 kernels were bitter. In 133 families (4206 seedlings), all the trees gave sweet kernels. In 19 progenies, a proportion of 79.24 per cent of sweet and 20.76 per cent of bitter almonds was recorded. This proportion is close to the expected (75:25 per cent sweet:bitter), as the kernel taste is considered to be controlled by a gene, sweet being dominant. From the information obtained analysing these 19 families, 18 cultivars were classified as heterozygous. On the other hand, in 81 of the analysed crosses, at least one of the parents was heterozygous. The study of these progenies and the knowledge of the origin of some of the cultivars used as parents, has also allowed 20 cultivars to be classified as homozygous for sweetness.
11. GREMPA Seminar on Pistachios and Almonds, 1999/09/01-04, Sanliurfa (Turkey)